Long-term dynamics of a Cladocora caespitosa bank as recorded by a Posidonia oceanica millenary archive. (5th August 2021) - Monnier, Briac; Lehmann, Léa; Sartoretto, Stéphane; Pergent-Martini, Christine; Mateo, Miguel Ángel; Pergent, Gérard
Abstract: Along most Mediterranean coasts, the endemic seagrass species Posidonia oceanica builds extensive meadows and complex peat-like bioconstruction known as 'mattes'. These belowground deposits are recognized as a valuable long-term archive allowing the reconstruction and the study of palaeo-climatic and palaeo-ecological changes in the coastal environment over the Holocene period. One of the P. oceanica matte cores sampled during a coring survey along the eastern continental shelf of Corsica Island (France, NW Mediterranean) revealed the unprecedented finding of a dead bank of the scleractinian coral Cladocora caespitosa embedded in the matte. Measurement of the morphological and biometrical features of corallite fragments coupled to biogeosedimentological analysis and radiocarbon dating contributed to provide a basis for the reconstruction of the stratigraphic sequence since the mid-Holocene (last 4750 years). The study of the sediment core enabled identification of three major phases: (i) the settlement of the C. caespitosa colonies (~4750-3930 cal yr BP), (ii) the coexistence of the C. caespitosa bank and the P. oceanica meadow (~3930-1410 cal yr BP), followed by (iii) the death of the coral bank and the development of only the P. oceanica meadow (~1410 cal yr BP-present). The sclerochronological analysis completed on the well-preserved corallite fragments revealed that the mean annual growth rate of the coral ranged between 1.9 and 3.1 mm yr −1 with a mean value estimated at 2.3 ± 0.8 mm yr −1 . Trend analysis showed semi-millennial to millennial oscillations in annual growth rates which are probably related to environmental climatic changes since the Cold Phase of the Subatlantic period (2925-2200 cal yr BP). During the Roman Warm Period (2200-1500 cal yr BP), the decline and the death of the bank (~1410 cal yr BP) was probably due to the combined effect of a prolonged increase in summer temperatures and an increase in the competition with the P. oceanica meadow. Graphical abstract: Image 1 Highlights: Finding of a C. caespitosa coral palaeo-bank embedded in the matte of P. oceanica . Palaeoenvironmental reconstruction of the sequence since the mid-Holocene. Sclerochronological analysis revealed a coral mean growth rate of 2.3 ± 0.8 mm yr −1 . Growth pattern fluctuations shown to be related to abiotic and climatic conditions. Bank death was probably due to prolonged SSTs during the Roman Warm Period.